The contribution to total power output from the arms and legs using a new whole-body swimming training machine - Swaine, I. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
A new whole-body swimming training machine can be used to determine the power generated by each limb. The contribution made by each limb to the total power output can be calculated (%) in relation to exercise intensity. 12 swimmers with a mean age of 23.2 * 1.2 (yrs), stature 1.75 * 0.02 (m) and body mass of 73.8 * 2.9 (kg) gave informed consent and performed an incremental whole-body exercise test to exhaustion on the computer-interfaced whole-body swimming training machine. Exercise intensity commenced at 100W and was increased by 50W per minute. Peak oxygen consumption (VO2peak) and peak power output (Wpeak) were determined. The mean values of VO2peak and Wpeak were; 3.7 * 0.8 l/min and 366.7 * 52.6 W respectively. At various exercise intensities the relative contribution of the legs to total power output was as follows: At 20%VO2peak it was 29.7 %, at 40%VO2peak it was 35.8%, at 60%VO2peak it was 41.7% and at 80%VO2peak it was 48.2%. At VO2peak itself, the contribution was 53.5%. These results show that the contribution of the legs (to total power output) can be as much as the contribution from the arms, during high intensity exercise in swimmers. Of course, the extent to which these results can be applied to swimming is limited by the specificity of the exercise, but the results suggest that swimmers can perhaps produce as much power with their legs as they can with their arms, when they exercise with their arms and legs simultaneously.